2022
DOI: 10.3390/ani12151916
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Raptor Admission to the Wildlife Rehabilitation Centre in Abruzzo (Central Italy) from 2005–2016

Abstract: The purpose of this retrospective study was to describe the causes of morbidity and mortality in free-ranging raptors admitted to a wildlife rehabilitation center (WRC) in Abruzzo Italy from 2005 to 2016 and the associated risk factors. A total of 2496 free-ranging raptors were included in the study. We analyzed the raptors’ medical records, epidemiological information, bird characteristics, cause of admission, final diagnosis, and outcome. The prevalence rates of nocturnal and diurnal raptors were 49% and 51%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Although animal ecology, biology, and behaviour appear to predispose certain species of animals to certain threats [ 16 ], and one might expect some variation in admissions according to the geographical location of the WRC, studies from WRCs across the world showed some common trends. Although there are some differences in the groupings of reasons for admission, ‘orphans’ are numerous in most studies and were the second most common cause for admissions in many studies [ 2 , 12 , 16 , 33 , 67 , 68 ]. The primary reason for admission was frequently some classification of ‘injury ‘or ‘trauma’ or ‘anthropogenic causes’; for example, 34.6% of admissions in Athens, Greece, were classified as an ‘unknown accident’ [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although animal ecology, biology, and behaviour appear to predispose certain species of animals to certain threats [ 16 ], and one might expect some variation in admissions according to the geographical location of the WRC, studies from WRCs across the world showed some common trends. Although there are some differences in the groupings of reasons for admission, ‘orphans’ are numerous in most studies and were the second most common cause for admissions in many studies [ 2 , 12 , 16 , 33 , 67 , 68 ]. The primary reason for admission was frequently some classification of ‘injury ‘or ‘trauma’ or ‘anthropogenic causes’; for example, 34.6% of admissions in Athens, Greece, were classified as an ‘unknown accident’ [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Trauma also accounted for 27.8% of morbidity in all birds in Gran Canaria, Spain [ 53 ] and 18.14% of morbidity, specifically in seabirds [ 71 ]. Several studies considering raptor admissions alone, in the UK [ 17 , 72 ] and elsewhere [ 64 , 67 , 68 , 73 , 74 , 75 , 76 , 77 ], found trauma to be one of the two most common reasons, alongside orphans, for admissions. Trauma is also commonly cited as a reason for admissions to WRCs for specific species of mammals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The risk of collisions between raptors and motor vehicles is increased by the fact that some species of raptors feed on the carcasses of animals hit by motor vehicles on highways [29]. Injuries were also reported among the most frequent reasons for the admission of raptors to rescue centres in other studies [30]. Traumatic injuries, not further specified, were the reason for the treatment of 75.80% (402) of raptors admitted to a rescue centre in Greece in the years 1997-2000 [31] and 49% (7,021) of raptors admitted to a rescue centre in Spain [32].…”
Section: Reasons For Admission Of Raptors To Rescue Centresmentioning
confidence: 96%